The Importance of Human Inequalities and Health Care Quality in Life Expectancy of Countries - Kandemir, Orhan (Sciedu Press, 2016)
In Human Development Reports published by The United Nations Development Programme (UNDP), the development in the health dimension is measured by life expectancy at birth. In the context of this study, factors that affect life expectancy in 130 countries were analyzed with the help of established multiple regression model. The independent variables of the model, except the proportion of health expenditure in GDP, human inequality, gross national income per capita and satisfaction with health care quality are found to be statistically significant. This situation indicates that the quality of health services in the country in terms of life expectancy is more important than the amount of health care expenditures. The most influential variables on life expectancy at birth were found in order as; human inequality, gross national income per capita and satisfaction with health care quality.
Keywords: 8. Economic growth; 1. No poverty; 10. No inequality; 3. Good health